Penerapan Pasal 3 Angka 11 Peraturan Pemerintah Nomor 53 Tahun 2010 Tentang Disiplin Pegawai Negeri Sipil Di Kabupaten Ende - Ernesta Arita Ari (Jayapangus Press, 2021)
Civil servants as state servants and public servants are required to be loyal and obedient to Pancasila, the 1945 Constitution, the State and the Government. Therefore, every civil servant must have the ability, quality and high discipline. The ability referred to is not only the ability in the field of skill, but must be supported by the total level of self-quality, because the quality of a Civil Servant is determined by knowledge, skills, and mental attitude (Attitude). With that, it is necessary to increase the utilization of the state apparatus, especially those related to quality, service efficiency and protection to the community as well as professional skills in supporting the implementation of their duties. To achieve this goal, the government has issued a Regulation on Discipline, namely Government Regulation Number 53 of 2010 concerning Civil Servant Discipline. In the regulation of Article 3 point 11 regulates the compulsory work attendance by complying with the working hours of Civil Servants. However, in practice there are still civil servants in the local government of Ende who violate this obligation.